2006
DOI: 10.1007/s00415-006-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

CSF prostaglandin D synthase is reduced in excessive daytime sleepiness

Abstract: Lipocalin-type prostaglandin D synthase (L-PGDS) is a brain enzyme, which produces prostaglandin D(2), a substance with endogenous somnogenic effects. Using a standardized protocol for immunonephelometric determination of cerebrospinal fluid (CSF) L-PGDS levels, we show that CSF L-PGDS levels are significantly lower in 34 patients with excessive daytime sleepiness when compared with levels in 22 healthy controls. Thus, L-PGDS may represent the first neurochemical measure of excessive daytime sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…PGDS is an enzyme necessary for the production of prostaglandin D 2 (PGD 2 ), a substance with somnogenic activity in mammals (Huang et al 2007). The infusion of selective inhibitors of PGDS reduces sleep amounts in rats, concomitant with a reduction of PGD 2 content in the brain (Qu et al 2006), and serum PGDS concentrations are reduced during both enforced sleep deprivation as well as during excessive daytime sleepiness in humans (Jordan et al 2004;Bassetti et al 2006). Thus, the differential expression of PGDS during sleep restriction in the sparrow suggests that prostaglandin D 2 may play a similar role in avian sleep regulation.…”
Section: Discussionmentioning
confidence: 99%
“…PGDS is an enzyme necessary for the production of prostaglandin D 2 (PGD 2 ), a substance with somnogenic activity in mammals (Huang et al 2007). The infusion of selective inhibitors of PGDS reduces sleep amounts in rats, concomitant with a reduction of PGD 2 content in the brain (Qu et al 2006), and serum PGDS concentrations are reduced during both enforced sleep deprivation as well as during excessive daytime sleepiness in humans (Jordan et al 2004;Bassetti et al 2006). Thus, the differential expression of PGDS during sleep restriction in the sparrow suggests that prostaglandin D 2 may play a similar role in avian sleep regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that, in humans, histaminergic transmission may also fluctuate according to sleep pressure and decrease in the presence of EDS. Similarly, a downregulation was postulated to explain the recent observation of low levels of CSF prostaglandin D synthase, a brain enzyme with somnogenic effects, in 34 patients with narcolepsy and other forms of EDS (Bassetti et al ., 2006). In sum, low CSF histamine levels may result from an interaction between histaminergic neurons and different arousal (monoaminergic) systems and/or the cytokine/prostaglandins system (Bassetti et al ., 2006; Urade and Hayashi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…271 Bassetti et al . 272 reported that CSF levels of L-PGDS are significantly lower in patients (n = 34) with excessive daytime sleepiness, when compared with levels in healthy controls (n = 22). Barcelo et al 273 reported that serum levels of L-PGDS are higher in obstructive sleep apnea patients with excessive daytime sleepiness than those without excessive daytime sleepiness.…”
Section: Prostaglandin D Synthases (Pgdss)mentioning
confidence: 95%